Solar Flare and Geomagnetic Storm Effects on the Thermosphere and Ionosphere During 6–11 September 2017. Issue 3 (26th March 2019) - Qian, Liying; Wang, Wenbin; Burns, Alan G.; Chamberlin, Phillip C.; Coster, Anthea; Zhang, Shun‐Rong; Solomon, Stanley C.
Abstract: The period of 6–11 September 2017 was an active period in which multiple solar flares and a major geomagnetic storm occurred. The two largest flares, an X9.3 and an X8.2, were a disk flare and a limb flare, respectively. We conducted model simulations and data analysis to examine solar flare effects on the coupled thermosphere and ionosphere (TI) system in connection with flare location effects and to investigate the occurrences of large‐scale traveling atmosphere disturbances (TADs) due to flares and storms. Soft X‐ray enhancement, which dominates E region ionization, is essentially not affected by the location of a flare on the Sun; solar extreme ultraviolet enhancement, which dominates ionization above ~150 km, is much weaker for a limb flare compared to a disk flare with the same magnitude. Consequently, flare responses in the lower thermosphere, and ionosphere E region are not affected by flare locations, but above ~150 km, the TI system responds more strongly to disk flares than to limb flares. However, our studies show that during the space weather events in September 2017, these flare location effects were masked by other factors including local time and longitude. Large‐scale TADs occurred when there were both flares and storms. The presence of the flares changed the magnitudes and propagation speeds of the large‐scale TADs. However, there was no evidence that large‐scale TADs occurred when there were only flares and not storms, indicating that solar flares alone were not sufficient to excite large‐scale TADs. Key Points: Flare location effects were masked by geophysical conditions including local time and longitude Solar flares changed the amplitudes and propagation speeds of TADs excited by storms Solar flares alone were not the sufficient conditions to excite large‐scale TADs